Long-term dynamics of Methone, Anthe and Pallene - Callegari, Nelson [UNESP]; Yokoyama, Tadashi [UNESP] (Cambridge Univ Press, 2010)
We numerically investigate the long-term dynamics of the Saturn's small satellites Methone (S/2004 S1), Anthe (S/2007 S4) and Pallene (S/2004 S2). In our numerical integrations, these satellites are disturbed by non-spherical shape of Saturn and the six nearest regular satellites. The stability of the small bodies is studied here by analyzing long-term evolution of their orbital elements.We show that long-term evolution of Pallene is dictated by a quasi secular resonance involving the ascending nodes (12) and longitudes of pericentric distances (pi) of Mimas (subscript 1) and Pallene (subscript 2), which critical argument is pi(2) - pi(1) - Omega(1) + Omega(2) Long-term orbital evolution of Methone and Anthe are probably chaotic since: i) their orbits randomly cross the orbit of Mimas in time scales of thousands years); ii) long-term numerical simulations involving both small satellites are strongly affected by small changes in the initial conditions.
Keywords: Celestial Mechanics; planets and satellites; individual (Saturn, Aegaeon, Methone, Anthe, Pallene); methods; numerical